2005
DOI: 10.2989/17280580509486602
|View full text |Cite
|
Sign up to set email alerts
|

Visual-motor integration functioning in a South African middle childhood sample

Abstract: Visual-motor integration functioning has been identified as playing an integral role in different aspects of a child's development. Sensory-motor development is not only foundational to the physical maturation process, but is also imperative for progress with formal learning activities. Deficits in visual-motor integration have been identified as precursors of later learning disabilities and other neurological conditions. The primary aim of this study was to determine the status of visual-motor integration fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
3
21
0
2
Order By: Relevance
“…Significant differences were also indicated between the academic mastery of the different SES school types ( P < 0.01), indicating that most of the children classified in the no‐mastery category or in the poor academic performance category (Table ) were in Quintiles 1–3 schools that represented the low SES type schools. Lotz and colleagues () indicate a relationship between visual‐motor integration, SES and mastering of reading, writing and arithmetic at school entrance level, substantiating these results. A meta‐analysis performed by Duncan and colleagues () furthermore indicate that early math skills have the greatest predictive power of school readiness, followed by reading and then attention, which not only substantiate our findings, but also highlight the importance of proper attention to the underlying success factors in early math success such as visual‐motor integration, visual perception and kinaesthetic awareness.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Significant differences were also indicated between the academic mastery of the different SES school types ( P < 0.01), indicating that most of the children classified in the no‐mastery category or in the poor academic performance category (Table ) were in Quintiles 1–3 schools that represented the low SES type schools. Lotz and colleagues () indicate a relationship between visual‐motor integration, SES and mastering of reading, writing and arithmetic at school entrance level, substantiating these results. A meta‐analysis performed by Duncan and colleagues () furthermore indicate that early math skills have the greatest predictive power of school readiness, followed by reading and then attention, which not only substantiate our findings, but also highlight the importance of proper attention to the underlying success factors in early math success such as visual‐motor integration, visual perception and kinaesthetic awareness.…”
Section: Discussionmentioning
confidence: 68%
“…Visual perception, visual‐motor integration and motor proficiency are important foundational skills for a child's school readiness (Beery ), where deficits in any of these areas can interfere with academic success (Bowman & Wallace ; Kattouf & Steele ; Orfield ; Sortor & Kulp ; Lotz et al . ; Goddard‐Blythe ; Van Hoorn et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…There are few cognitive screening tools for young children in Sub-Saharan Africa and this test was considered the most appropriate. This revised version of DAP has been previously used in African countries [3032]. Additionally, the use of a nonverbal, quick and easy-to-administer task has the advantage of eliminating potential sources of bias, including primary language, verbal skills, or communication difficulties.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to the South African context, research on the previous versions of these tests have found unique differences in the South African population [32][33][34][35][36][37][38][39][40] . Differences in the performance of South African children as compared to the American norms were identified in the Beery VMI and DTVP-2, TVPS-R where children would score above, average or below average on certain subtests.…”
Section: © Sa Journal Of Occupational Therapymentioning
confidence: 99%
“…For example, in a study conducted in Singapore using the fifth edition of the Beery VMI, a significant difference between the performance of the Singaporean pre-schoolers and the standardised sample of American children was found 18 . Unique differences were also observed among South African children [32][33][34][35]39 , such as: some of the SA population presenting with lower test performance 35 , or higher performance in the Motor Coordination subtest than the American normative sample 33 , and performance differences observed in environmentally disadvantaged 34 and socio-economic status groups 32 .…”
Section: Beery Vmimentioning
confidence: 99%